Understanding the health-disease process and the birth of Social Medicine (Jornal Memorial da Medicina, 2020)
Social Medicine was born from the discussion in the 19th century about the health-disease process, being one of the precursors of health promotion, in which it was seen as a technology of the time for the health-disease process of the population. The health-disease process transforms over time, in which it is essential to have a universal thought that understands that the gradients of mortality and morbidity involve socioeconomic classes. The purpose of this review is to revisit the theories that have grounded the definitions of the health-disease process throughout the history of mankind and the contribution of social medicine to the current context of collective health. It is relevant to address that the living and working conditions of the population were directly linked to their health situation, social, cultural, and psychological factors that influence the occurrence of diseases and illnesses. Therefore, promotion, prevention, cure, and rehabilitation were initial measures based on health education and actions used by the State. Moreover, the field of social medicine strongly contributed to improve and implement the model of primary health care (PHC), focused on the community, considering the social determinants of the health situation of the communities, in addition to the individual aspects of each being.